The effects of isokinetic contraction velocity on concentric and eccentric strength of the biceps brachii - Drury, D. G.; Stuempfle, K. J.; Mason, C. W.; Girman, J. C. (The Journal of Strength and Conditioning Research, 2006)
The purpose of this investigation was to determine the influence of contraction velocity on the eccentric (ECC) and concentric (CON) torque production of the biceps brachii. After performing warm-up procedures, each male subject (n = 11) completed 3 sets of 5 maximal bilateral CON and ECC isokinetic contractions of the biceps at speeds of 90, 180, and 300°·s-1 on a Biodex System 3 dynamometer. The men received a 3-minute rest between sets and the order of exercises was randomized. Peak torque (Nm) values were obtained for CON and ECC contractions at each speed. Peak torque scores (ECC vs. CON) were compared using a t-test at each speed. A repeated measures analysis of variance was used to determine differences between speeds. ECC peak torque scores were greater than CON peak torque scores at each given speed: 90°·s-1, p = 0.0001; 180°·s-1, p = 0.0001; and 300°·s-1, p = 0.0001. No differences were found between the ECC peak torque scores (p = 0.62) at any of the speeds. Differences were found among the CON scores (p = 0.004). Post hoc analysis revealed differences between 90°·s-1 (114.61 ± 23) and 300°·s-1 (94.17 ± 18). These data suggest that ECC contractions of the biceps brachii were somewhat resistant to a force decrement as the result of an increase in velocity, whereas CON muscular actions of the biceps brachii were unable to maintain force as velocity increased.